Central African Republic : First Review of the Arrangement Under the Extended Credit Facility, Financing Assurances Review and Request for Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Central African Republic's First Review of the Arrangement Under the Extended Credit Facility (ECF), Financing Assurances Review and Request for Waiver of Nonobservance of Performance Criterion (PCs). Program implementation through the end of August has been satisfactory. All quantitative and indicative targets were met, with the exception of the criterion on nonaccumulation of external payments for which the authorities are taking corrective measures. Improvement in tax revenue, albeit in line with the program target, remains fragile. The IMF staff supports completion of the first review under the ECF arrangement and the authorities' request for a waiver for the nonobservance of a PC. The IMF staff also recommends that the financing assurances review be completed.